1993
DOI: 10.3109/01485019308988401
|View full text |Cite
|
Sign up to set email alerts
|

Epididymal Markers in an Andrology Clinic

Abstract: The ability of the markers alpha-glucosidase, carnitine, and glycerylphosphorylcholine to indicate epididymal obstruction was studied. alpha-Glucosidase was found to be the best discriminant, with 93.4% correct classifications. The possible interrelationship between alpha-glucosidase activity, sperm ATP, and epididymal function was then studied. alpha-Glucosidase correlated positively with the percentage of motile sperm (p = 0.0212) and with the percentage of sperm with good forward progression (p = 0.0374), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Thus, the more the amount of sperm was, the higher the concentration of alpha-glucosidase in epididymis. There was a correlation between the level of alpha-glucosidase and sperm motility, especially significant correlation between the level of alpha-glucosidase and the sperm progressive motility [7][8][9]11]. However, our data showed that there was no any apparent correlation between the alpha-glucosidase activity in seminal plasma and total motile sperm or grades a and b motile sperm, similar to some other studies [11].…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the more the amount of sperm was, the higher the concentration of alpha-glucosidase in epididymis. There was a correlation between the level of alpha-glucosidase and sperm motility, especially significant correlation between the level of alpha-glucosidase and the sperm progressive motility [7][8][9]11]. However, our data showed that there was no any apparent correlation between the alpha-glucosidase activity in seminal plasma and total motile sperm or grades a and b motile sperm, similar to some other studies [11].…”
Section: Discussionsupporting
confidence: 87%
“…Of these substances, neutral a-glucosidase activity positively correlated with conventional sperm characteristics including motility and progressive sperm motility [4]. The enzyme activity is low in patients with inefficient epididymal hnction and in patients with obstruction of the excretory ducts [3].…”
mentioning
confidence: 99%
“…Neutral a -GLI is almost exclusively produced by the epididymis and has been used clinically as a marker of its function [10,11]. This enzyme may be involved in the preparation of sperm for storage rather than in development of fertilizing capacity in the rat [26].…”
Section: Discussionmentioning
confidence: 99%